Conceptual framework for project governance of public sector infrastructure project in Pakistan - Khan, Asadullah; M., Waris; Ishak, Ismail; Adeleke, A. Q.; Ahmed, Ifzal (Future Academy, 2019)
Project governance has become an important subject matter for both the project management environment and the public sector, due to the demands for enhanced project performance. Project professionals in developing countries encounter various challenges while execution of the projects. This paper has analyzed previous studies on Infrastructure development projects and project management practices in Pakistan published in academic journals and conference proceedings. The study reveals the organizational shortfalls and various challenges in the procedures adopted for planning and managing infrastructure projects. As the infrastructural development projects play a key role in the economic growth of developing economies like Pakistan, successful implementation of the projects is, therefore, not only essential but inevitable to achieve development goals. This study identifies the shortcomings and proposes project governance framework for infrastructure development projects, which will enhance the project performance and facilitate the various public-sector organizations, donor agencies involved in policy-making, planning and implementation of development projects.